Pedicled Abdominal Flap in the Youngest Patient Yet? A Case Report of a Newborn with Neonatal Compartment Syndrome - Sabapathy, S. Raja; Dharanipriya, A.; Mohan, Monusha; Ramani, Subramanian; Selvaraj, M.; Shanmuga Krishnan, R. Raja (Indian Journal of Plastic Surgery, 2025)
Pedicled abdominal flaps continue to be popular in most parts of the world for covering soft tissue defects of the upper limb. There is apprehension if distant pedicled flaps can be used in children for fear of disruption. We recently had a newborn baby with neonatal compartment syndrome (NCS) of her left upper limb in whom a pedicled abdominal flap was successfully used to cover the raw area in the forearm at 41 days of life. A severely swollen limb with ischemic skin lesions associated with lack of motion of the upper limb often points to NCS. Since no guidelines exist for the diagnosis and management of NCS, a high index of suspicion and urgent fasciotomy are required to limit its sequelae. Our patient had an emergency fasciotomy elsewhere was referred to us with a precariously viable limb for salvage. The raw area in the forearm with exposed bone was successfully covered with a pedicled abdominal flap at 41 days of life. Our patient is probably the youngest patient ever to receive a pedicled abdominal flap.
Keywords: neonatal compartment syndrome; fasciotomy; pedicled flap; children; abdominal flap